Penerapan Metode Latihan Drill Shooting menggunakan Punggung Kaki dan Kaki Bagian Dalam terhadap Kecepatan dan Ketepatan Shooting Futsal. - Rexi Rizkia Syofyan; Kardjono Kardjono; Nida’ul Hidayah (Jurnal Kepelatihan Olahraga, 2022)
Abstract This study aims to determine the difference between the application of the drill shooting training method using the instep and shooting using the inside of the foot on the speed and accuracy of futsal shooting for Futsal Athletes at the Bassuran Muda U-16 Jakarta Academy. This research is using experimental method. In this study, there were two groups, namely: the group that applied the drill shooting method using the instep and the group that did the shooting using the inside of the foot on the speed and accuracy of shooting. The sample used in this study were the core players in the Academy Bassuran Muda U-16 Jakarta, totaling 20 people using a proposive sampling approach. The instruments used are pre-test and post-test of shooting speed and accuracy using two shooting stances, namely shooting using the instep and shooting using the inside of the foot. The results of this study indicate that there is a significant effect of drill shooting exercise using the instep and inner foot on increasing the speed and accuracy of shooting futsal, but there is no significant difference in drill shooting exercise using the instep with the inner foot on the speed and accuracy of shooting futsal. on the Futsal Athletes at the Youth Bassuran U-16 Academy in Jakarta